A DEVELOPMENT PLAN FOR TOURISM POTENTIALS IN COASTAL AREA OF UJUNGNEGORO, BATANG REGENCY - Suzzana Ratih Sari; Edy Darmawan (JOURNAL OF COASTAL DEVELOPMENT, 2006)
Ujungnegoro is one coastal area in Batang Regency Central Java, which offers a unique environmentalsetting as well as enormous tourism potentials such as marine resources, aquaculture and plantations.Furthermore, Ujungnegoro has a variety of terrain ranging from plain to hills. Despite these potentials,presently the government faces some problems which hinder the development of tourism in this area,namely limited capital for development purposes, absence of infrastructure, inadequate governmentassistance in terms of budgeting and technical assistance. This paper analyzes these problems andidentifies appropriate planning strategies that may be adopted to promote the tourism industry inUjungnegoro, Batang Regency. These strategies will hopefully evolve into policies that will develop thisarea into uppropriate tourist destination. Should this come to pass, this area will provide a greatercontribution to the development of the area as a whole.